Pneumonitis in cancer patients receiving anti-PD-1 and radiotherapies: Three case reports. Issue 1 (January 2017) - Lu, Chieh-Sheng; Liu, Jin-Hwang
Abstract: Introduction: In development of novel therapies for the treatment of patient with cancer, the use of radiotherapy (RT) can produce significant local control and, in recent studies, has also been shown to mediate anti-tumor responses at distant sites by triggering and enhancing the endogenous cellular immune responses. Although RT induces an abscopal effect in some patients due to enhanced immune response to the tumor, immune-escape mechanisms, including up-regulation of programmed death-ligand 1 (PD-L1) on tumor cells, limit this benefit in other patients. Hence, many studies have promoted the synergy of RT and anti-programmed cell death protein 1 (PD-1) treatment for antitumor immunity. However, outcome may be improved when more therapies are combined, but risk of side effects can be increased. Case Presentation: We herein present 3 advanced cancer patients with pulmonary metastasis and who received RT. Later, they underwent anti-PD-1 treatment and unfortunately suffered from anti-PD-1-related pneumonitis over the nonirradiated areas after 4 cycles of treatment. The upregulation of cellular PD-1 expression in these areas was considered and the immune overreaction by anti-PD-1 treatment may cause these severe pulmonary adverse effects. Conclusion: Our review of 3 cases warrants careful workup to reduce the risk of side effects by combinative therapy with RT and anti-PD-1 treatment.